Iminoenamine based novel androgen receptor antagonist exhibited anti-prostate cancer activity in androgen independent prostate cancer cells through inhibition of AKT pathway. (25th September 2017) - Divakar, S.; Saravanan, K.; Karthikeyan, P.; Elancheran, R.; Kabilan, S.; Balasubramanian, K.K.; Devi, Rajlakshmi; Kotoky, J.; Ramanathan, M.
Abstract: Treatment by androgen receptor (AR) antagonists is one of the regimens for prostate cancer. The prolonged treatment with AR antagonist leads to the expression of point mutation in the ligand binding domain of the AR. This point mutation causes resistance to AR antagonist by converting them into an agonist. The T887A mutated AR was frequently expressed in androgen independent prostate cancer (AIPC) patients. Through literature survey and molecular modelling, we have identified a novel AR antagonist having a bulky β-iminoenamine BF2 complex scaffold. The tested and standard ligands were screened in AR positive (LNCaP, MCF-7 and MDA-MB-453), AR negative (PC3), and non-cancerous (3T3) cell lines through anti-proliferation assay. The ligand, ARA3 was the most potent molecule among all the tested ligands and was 7.6 folds selective for AR positive cell lines. The mechanism of anti-prostate cancer activity of ARA3 was confirmed by western blot, qPCR, and apoptotic assays in LNCaP (T887A positive AR) cells. Structural activity relationship was derived by correlating the in-vitro and in-silico data. Consequently, we have identified the essential functional groups that could prevent the resistance concerning mutant AR. The ARA3 induces the apoptosis in AIPC cells by preventing the AR mediated activation of AKT pathway. The bicalutamide did not induce the apoptosis because it failed to prevent the AR mediated activation of AKT. Highlights: Identification of novel β-iminoenamine BF-2 complex as androgen receptor antagonist. The test ligand ARA3 is ∼8 times potent than bicalutamide a known AR antagonist. β-iminoenamine interactions with helix 12 of the androgen receptors favors activity. The ARA3 induces apoptosis through inhibition of AKT activation.